Claiming Heritage, Renewing Authority - Catharina Raudvere (European Journal of Turkish Studies)
This article discusses the role and status of Sufi groups in Bosnia-Herzegovina today, an issue where Turkish influences are unavoidable, irrespective of whether the focus is on conceptions of the Balkans’ Ottoman legacy or on contemporary arenas for religious alternatives in public life. Today old Sufi establishments face competition from groups with roots abroad both in terms of community leadership and the relationship between the individual groups and the state administration. Sufi-orientated activities play a role within the established Muslim congregations, the ritual aspects in particular attracting previously non-practicing Muslims. Many aspects of the Sufi theme can and should of course be related to the region’s Ottoman past, the authoritarian repression of religion in the Yugoslav Federation, and the war in the 1990s. These particular features have had an impact on religious practices as well as on the institutional organisation of Islam in the region.The attraction of the Sufi groups active today in Bosnia comes from two sources: first, references to authentic tradition, charismatic leaders, fellowships and groups that offer lifestyles in line with Muslim conduct, and secondly, their tools for establishing independent theological interpretations and for highly individualised spirituality. Bosnian Sufi identity balances between national heritage (with or without political connotations) and a search for spirituality (with or without affiliation to a group or an order); it connects to the contemporary world and its specific issues in a way that is relevant for Bosnians today, as well as being symptomatic of late-modern religion worldwide.